ANALISIS PENGGUNAAN BIOADITIF MINYAK ATSIRI TERHADAP KONSUMSI BAHAN BAKAR DAN EMISI GAS BUANG PERTALITE SEPEDA MOTOR 4 LANGKAH - Donny Fernandez; Alfan Rifani; Wakhinuddin S; Toto Sugiarto (Ensiklopedia of Journal, 2022)
This study aims to analyze the results of mixing pertalite with essential oils on fuel consumption and exhaust emissions on motorcycles. the type of research method is experimental research. From the data obtained for ideal rotation using pure pertalite fuel the average fuel consumption is 1233 seconds/50 ml, one liter pertalite mixed with essential oils 1.2 ml averages 1234 seconds/50 ml, one liter pertalite mixed essential oil 1 ,8 ml average 1237 seconds per 50 ml, one liter pertalite essential oil 2.4 ml average1259 seconds per 50 ml. The results of the CO exhaust emission test using pure pertalite, 1.2 ml & 1.8 ml essential oils were 0.04% while the essential oil 2.4 ml was 0.03%. Emissions testing on pure Co2 pertalite was 1.77%, pertalite with 1.2 ml was 1.80%, pertalite with volatile oil 1.8% was 1.87%, pertalite with essential oil 2.4% was 2. 10%. The emission test at pure HC pertalite was 875 ppm, 1.2 ml was 759 ppm, 1.8 ml was 658 ppm, and 2.4 ml was 629 ppm. The results of the research data that the mixture of pertalite with 20% essential oil is the most efficient in fuel and exhaust emissions.Keywords: Essential Oil, Pertalite, Fuel consumption, exhaust emissions